1931 PA. Laws 498, No. 158, § 4 - (:unkn) unknown (General Publisher, 1931)
Prohibited individuals convicted of violent crimes from owning, possessing or having a firearm under their control.
--
Keywords: POSSESSION - DANGEROUS PERSONS